The Role of Cytokines in the Fibrotic Responses in Crohn’s Disease - Curciarello, Renata (2017)
Crohn?s disease is an idiopathic disorder of the gut thought to be caused by a combination of environmental and genetic factors in susceptible individuals. It is characterized by chronic transmural inflammation of the terminal ileum and colon, with typical transmural lesions. Complications, including fibrosis, mean that between 40 and 70% of patients require surgery in the first 10 years after diagnosis. Presently, there is no evidence that the current therapies which dampen inflammation modulate or reverse intestinal fibrosis. In this review, we focus on cytokines that may lead to fibrosis and stenosis and the contribution of experimental models for understanding and treatment of gut fibrosis.